Studies of Somatic Embryogenesis in Selected Clones of Eucalyptus Tereticornis - Gupta, Anupriya (My University, 2017)
Eucalyptus tereticornis is an important woody tree species belonging to family “Myrtaceae”. It is commercially valuable as it is used as a source of raw material for pulp and paper industry due to its important wood characteristics for the manufacture of high grade paper. The present study was focused on development of somatic embryogenesis protocol for selected elite clone of Eucalyptus tereticornis. The effect of plant growth regulators (BA, NAA and 2, 4-D) on somatic embryos induction from leaf and internodal explants taken from microshoots of E. tereticornis was evaluated. Maximum frequency of somatic embryo induction was observed on MS medium supplemented with NAA (5µM) and BA (5µM). It was noteworthy, that all combinations of BA with 2,4-D and NAA with 2,4-D resulted in callus induction. This callus was not found to be embryogenic in nature. The explants showing embryogenic structures were transferred to MS medium supplemented with 1µM GA3 and 1µM BA for germination. Various developmental stages of somatic embryo were observed through histological and scanning electron microscopic studies. The present study indicated the importance of plant growth regulators in embryo development and germination in woody plants.
Keywords: NAA, BA, Eucalyptus, somatic embryogenesis, callus